Efficiency Dynamics of Sugar Industry of Pakistan. (The Pakistan Development Review, 2009)
Pakistan is the 15th largest producer of sugar in the world, 5th largest in terms of area under sugar cultivation and 60th in yield. The sugar industry is the 2nd largest agro based industry which comprises of 81 sugar mills. With this scenario, Pakistan has to import sugar which exposes it to the effects of shortage and rising prices in the world. The present sugar crisis has opened up new avenues for researcher to analyse the performance and efficiency of the firms in this sector. Total factor productivity plays a significant role in measuring the performance of a firm which ultimately affects the shareholder’s value. This paper analyses the performance of sugar firms in Pakistan and estimate/calculate the Malmquist total factor productivity growth indices using non-parametric approach. TFP growth is further decomposed into technical, scale and managerial efficiency change using balanced panel data of 20 sugar firms listed on Karachi Stock Exchange for the period 1998 to 2007. The results reflect a tormenting picture for the sugar industry. Overall sugar industry improved technological progress by 0.8 percent while managerial efficiency change put a negative effect on the productivity by a same percentage; as a result the overall total factor productivity during 1998-2007 remained almost static with a decline of 0.1 percent. The analysis of TFP and its sources in individual year for overall sugar industry also presents divergent trend. The research suggests that sugar industry is facing serious productivity growth problems where no increase is recorded in total factor productivity during 1998 to 2007. The sugar industry is lacking in terms of managerial efficiency which could be explained by a general reduction in the quality of managerial decision-making among the best practice firms. Regardless of the reason for this decline, it has potentially serious implications for the longer-term financial viability of these sugar firms. The pattern of TFP growth tends to be driven more by technical change (or technical progress) rather than improvements in technical efficiency.